Sources of investment inefficiency: The case of fixed-asset investment in China - Duo Qin; Haiyan Song (Queen Mary University of London, Department of Economics, 2007)
This study attempts to measure the inefficiency associated with aggregate investment in a transitional economy. The inefficiency is decomposed into allocative and production inefficiency based on standard production theory. Allocative inefficiency is measured by disequilibrium investment demand. Institutional factors are then taken into consideration as possible explanatory variables of the disequilibrium. The resulting model is applied to Chinese provincial panel data. The main findings are: Chinese investment demand is strongly receptive to expansionary fiscal policies and inter-provincial network effects; and although there are signs of increasing allocative efficiency, the tendency of over-investment remains, even with improvements in production efficiency.
Keywords: E22; E62; H74; P3; C23; 330; Over-investment; Efficiency; Disequilibrium; Soft-budget constraint; Investition; Allokationseffizienz; Institutionelle Infrastruktur; Allgemeines Gleichgewicht; Systemtransformation; Sch\~AƒÂtzung; China